2019
DOI: 10.1002/adfm.201970107
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophilic Graphdiyne: Superhydrophilic Graphdiyne Accelerates Interfacial Mass/Electron Transportation to Boost Electrocatalytic and Photoelectrocatalytic Water Oxidation Activity (Adv. Funct. Mater. 16/2019)

Abstract: In article number https://doi.org/10.1002/adfm.201808079, Jin Zhang, Li‐Zhu Wu, and co‐workers describe the first superhydrophilic graphdiyne (GDY) electrode fabricated via air plasma for water oxidation. The resultant superhydrophilic CoAl‐LDH/GDY electrode shows superior oxygen evolution performance in both electrocatalytic and photoelectrocatalytic systems, which benefits from the facilitated interfacial mass/electron transportation by superhydrophilic GDY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…constructed CoAl–LDH/graphdiyne (CoAl–LDH/GDY) electrocatalysts/electrode with super‐wettable surface to increase the attractive ability toward H 2 O molecules. [ 95 ] The super‐wettability of CoAl–LDH/GDY was attributed to the hydrophilic oxygenic groups on GDY surface, which were introduced via plasma technology. According to DFT calculations, GDY with hydrophilic –COOH group on surface showed higher electron density, indicating that superhydrophilic GDY can be easily assembled with CoAl–LDH nanosheets.…”
Section: Electrocatalytic Application Of Transition‐metal‐based Ldh Mmentioning
confidence: 99%
“…constructed CoAl–LDH/graphdiyne (CoAl–LDH/GDY) electrocatalysts/electrode with super‐wettable surface to increase the attractive ability toward H 2 O molecules. [ 95 ] The super‐wettability of CoAl–LDH/GDY was attributed to the hydrophilic oxygenic groups on GDY surface, which were introduced via plasma technology. According to DFT calculations, GDY with hydrophilic –COOH group on surface showed higher electron density, indicating that superhydrophilic GDY can be easily assembled with CoAl–LDH nanosheets.…”
Section: Electrocatalytic Application Of Transition‐metal‐based Ldh Mmentioning
confidence: 99%
“…Li et al. [ 123 ] prepared superhydrophilic graphdiyne (GDY) electrodes by air plasma processing to support cobalt/aluminum layered double hydroxide (CoAl‐LDH/GDY) catalysts. The OER activity of CoAl‐LDH/GDY showed that only 258 mV overpotential was required to reach a current density 10 mA cm −2 , with a turnover frequency (TOF) of 0.60 s −1 at an overpotential of 300 mV.…”
Section: Effect Of Discharge Gas On Cbmsmentioning
confidence: 99%
“…c) J–V curves of hydrophobic GDY/BiVO 4 (purple), superhydrophilic GDY/BiVO 4 (blue), hydrophobic CoAl‐LDH/GDY/BiVO 4 (red), and superhydrophilic CoAl‐LDH/GDY/BiVO 4 (black). [ 135 ] Reproduced with permission. [ 135 ] Copyright 2019, Wiley‐VCH.…”
Section: Elements Complements and Combinations Of Oecsmentioning
confidence: 99%
“…Graphdiyne (GDY) turns superhydrophilic after air‐plasma treatment. [ 135 ] When attached to cobalt–aluminum layered double hydroxide (CoAl‐LDH) electrostatically, electrocatalytic and photoelectrocatalytic water oxidation rates are substantially raised compared to its hydrophobic counterpart (Figure 21b,c). The improvement in the PEC response by turning CoAl‐LDH/GDY/BiVO 4 superhydrophilic (≈1.34 times J ph at +1.2 V RHE ) is noticeably better than only turning GDY/BiVO 4 superhydrophilic (≈1.2 times J ph at +1.2 V RHE ), which means GDY is capable of activating more sites of CoAl‐LDH.…”
Section: Elements Complements and Combinations Of Oecsmentioning
confidence: 99%